2004
DOI: 10.1179/135100004225006029
|View full text |Cite
|
Sign up to set email alerts
|

Carnivorous pitcher plant uses free radicals in the digestion of prey

Abstract: A study of the involvement of free oxygen radicals in trapping and digestion of insects by carnivorous plants was the main goal of the present investigation. We showed that the generation of oxygen free radicals by pitcher fluid of Nepenthes is the first step of the digestion process, as seen by EPR spin trapping assay and gel-electrophoresis. The EPR spectrum of N. gracilis fluid in the presence of DMPO spin trap showed the superposition of the hydroxyl radical spin adduct signal and of the ascorbyl radical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 26 publications
0
27
0
Order By: Relevance
“…It has been suggested that prey proteins in the Venus flytrap are initially oxidized in order to facilitate their subsequent proteolysis (53), and it has been demonstrated that Nepenthes gracilis uses free radicals during the digestion process (54). Plumbagin, a low-molecular-weight compound present in Venus flytrap digestive fluid, likely facilitates this oxidation (40).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that prey proteins in the Venus flytrap are initially oxidized in order to facilitate their subsequent proteolysis (53), and it has been demonstrated that Nepenthes gracilis uses free radicals during the digestion process (54). Plumbagin, a low-molecular-weight compound present in Venus flytrap digestive fluid, likely facilitates this oxidation (40).…”
Section: Discussionmentioning
confidence: 99%
“…Class III peroxidases can generate highly reactive oxygen species (ROS) [20][21][22]. Chia et al also reported that ROS were produced in the Nepenthes pitcher fluid, and might aid in degrading proteins derived from the tissues of the prey [23]. Excess ROS cause oxidation reactions in proteins, such as crosslinking, and oxidized proteins are attacked by proteases.…”
Section: Discussionmentioning
confidence: 98%
“…ROS has additionally been shown to be involved in nutritive phagocytosis in starfish and other simple animals (Coteur et al 2002). In carnivorous pitcher plants, plant-secreted ROS plays a nutritional role in digestion of insect proteins (Chia et al 2004). Galek et al (1990) similarly reported that the ‘venus flytrap’ ( Dionaea muscipula ) employs ROS to pre-digest insect proteins prior to protease action on the denatured peptide fragments.…”
Section: Discussionmentioning
confidence: 99%